Rancang Bangun “Dolan Yuk” sebagai Discovery and Investation Platform untuk Pengembangan Pariwisata Kediri Berkelanjutan - Purwono, Prahoro Yudo; Ardiansyah, Fikky (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2024)
The public image of Kediri, which is still not optimal, has resulted in fewer visitors to specific tourist sectors. Additionally, poor management and marketing, along with inadequate investor absorption, are also complex issues. Furthermore, in some tourism sectors, Kediri still has many shortcomings, ranging from underutilizing existing tourism potential to fluctuations in visitor numbers, leading to a decline in the community's economic growth. Given these potentials, developing a sustainable tourism strategy with effective and efficient marketing is crucial to promote Kediri's public image locally and nationally. This research aims to describe the development of 'Dolan Yuk' as a marketing and tourism promotion platform and a means for the broader community to invest in the tourism sector, with a key focus on preserving and promoting the local culture. The research method used is a qualitative approach based on the ADDIE model. The research findings indicate that developing 'Dolan Yuk' is a stability strategy to develop Kediri's tourism potential better by attracting investors and visitors through various online offerings. This strategy is expected to preserve local culture while improving community welfare through tourism.